Discursive Construction of a (Trans)National Identity: Early Modern Illyrism - Blažević, Zrinka (2004)
Illyrism might be described as a discursive product of the South Slavic branch of the res publica litteraria which was since Humanism intensively engaged in the symbolic constructing of distinctive national identities. Intertextually and interdiscursively intertwined with the German Teutonism and Polish Sarmatism, early modern Illyrism represents both a discursive configuration of identity and a form of the symbolic political practice marked by high performative effects. Besides its textual and extratextual modalities, functions and meanings, this paper will focus on the ideological mechanisms and discursive strategies by virtue of which early modern Illyrism simultaneously constructs particular national, religious and political identities as well as an universal transnational Pan/South/Slavic identity.